Student Narratives on the Use of Artificial Intelligence to Enhance Creativity and Academic Writing Skills - Desy Liliani Husain; Rahayu Rahayu; Hanna Hanna (International Journal of Educational Narratives, 2026)
Background. The increasing integration of artificial intelligence (AI) into higher education has transformed students' approaches to learning, particularly in academic writing. While previous studies have primarily examined the effectiveness of AI-assisted writing, limited attention has been given to students' own narratives and lived experiences regarding how these technologies shape their creativity, confidence, and writing practices. Purpose. This study explores student narratives on the use of artificial intelligence tools to enhance creativity and academic writing skills. Specifically, it examines how undergraduate students at Halu Oleo University, Kendari, Southeast Sulawesi, describe their experiences of using AI writing tools in academic writing courses, focusing on idea generation, writing organization, language improvement, creative engagement, and self-confidence. Method. This study employed a qualitative narrative approach involving fifteen undergraduate students enrolled in an Academic Writing course. Data were collected through in-depth semi-structured interviews and analysis of students' reflective writing samples. Results. The findings reveal that students consistently described AI tools as valuable learning companions that facilitated idea generation, improved text organization, refined language quality, and strengthened confidence throughout the writing process. Their narratives also demonstrated increased creative engagement and greater willingness to revise and develop academic texts.   Conclusion. Student narratives suggest that artificial intelligence can serve as a meaningful pedagogical resource for enhancing creativity and academic writing skills when integrated within a supportive instructional framework. The findings emphasize that AI should complement rather than replace students' critical thinking and creative processes.